Nickel deposition on fluorinated, aromatic self-assembled monolayers: chemically induced cross-linking as a tool for the preparation of well-defined top metal films - Chesneau, Frédérick; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
We studied the deposition of metal atoms (Ni as a test adsorbate) on fluorinated self-assembled monolayers (SAMs) using films of perfluoroterphenyl-substituted alkanethiols, C6F5(C6F4)2(CH2)3SH (FTP3), and partly fluorinated alkanethiols, F(CF2)10(CH2)2SH (F10H2), on Au(111) as representative test systems. Unlike the F10H2 films, their FTP3 counterparts were found to stop efficiently the penetration of nickel atoms into the SAM. The primary process is the Ni-mediated loss of fluorine atoms followed by extensive cross-linking between the partly defluorinated FTP backbones. The stability of these backbones and the rapid development of the intermolecular cross-linking, affecting predominantly the topmost part of the FTP3 SAM, are the key components to hinder the metal penetration. The chemically induced cross-linking in combination with the entirely reactive SAM represents a new concept to prepare a well-defined metal film at the SAM-ambience interface. This can be useful in context of novel metal/SAM-insulator/metal assemblies that are of potential interest for electronic and spintronic applications.
Gesehen am 12.08.2020